Electro-mechanical coupled design of self-powered sensing systems and performances comparison through experiments - A. Somà; G. B. De Pasquale (Fracture and Structural Integrity)
Recent advances in low-power sensors and electronic components open to innovative strategies in structural monitoring and real-time data processing, in particular for industrial and vehicular fields. Dedicated devices for harvesting the energy dissipated by mechanical vibrations of machines are showing their applicability in supplying autonomous distributed sensing systems. The harvester will replace cables and storage batteries, with relevant benefits on the sensing system capillarity, accessibility and applicability. The design of the interfaces of the electric, magnetic and structural coupled systems forming the harvester include static and dynamic modeling and simulation of the interactions involved; smart and effective architectures are need to satisfy the general requirements of bandwidth, tunability and efficiency required by each application. This paper reports the research advances in this field as a result of laboratory tests and design studies, with particular focus on the design methodologies involved in the definition of energy harvesters.